CO 2 fertilization in temperate FACE experiments not representative of boreal and tropical forests - THOMAS HICKLER; BENJAMIN SMITH; I. COLIN PRENTICE; KRISTINA MJÖFORS; PAUL MILLER; ALMUT ARNETH; MARTIN T. SYKES (Global Change Biology, 2008)
Results from free‐air CO 2 enrichment (FACE) experiments in temperate climates indicate that the response of forest net primary productivity (NPP) to elevated CO 2 might be highly conserved across a broad range of productivities. In this study, we show that the LPJ‐GUESS dynamic vegetation model reproduces the magnitude of the NPP enhancement at temperate forest FACE experiments. A global application of the model suggests that the response found in the experiments might also be representative of the average response of forests globally. However, the predicted NPP enhancement in tropical forests is more than twice as high as in boreal forests, suggesting that currently available FACE results are not applicable to these ecosystems. The modeled geographic pattern is to a large extent driven by the temperature dependence of the relative affinities of the primary assimilation enzyme (Rubisco) for CO 2 and O 2 .